Helminto fauna de anfíbios da família Leptodactylidae em três fisionomias de Cerrado - Queiroz, Murilo de Souza [UNESP] (2015)
The parasites are an important role in maintaining local diversity of hosts and ecosystem functions, but they are the first organisms to disappear because of human activities on the natural environment. Knowledge of the biological diversity on the planet is still pretty scarce and inventory the fauna of a particular portion of an ecosystem is the first step for the conservation, recovery, and the rational use of the environment. Wildlife inventories, descriptions of species and helmintofaunas revisions are necessary because enrich the understanding of parasitism in vertebrate groups and form a basis for future studies. For the Mato Grosso do Sul state studies on helminth parasites are restricted to wetland region so the objectives of this study are to describe the helminth fauna associated with frogs in the Leptodactylidae family, estimate the parasitic infection parameters: prevalence, intensity of infection and wealth of parasites in three Cerrado physiognomies in Selvíria, Mato Grosso do Sul. We collected 114 frogs in a year of collections, with a total of 72 days in open traps and 48 hours of active search. Of the 114 hosts 89 were parasitized (78% prevalence) and were collected in 1730 helminths belonging to 21 species. Nematoda was the most diverse group (12 species), followed by Trematoda (9 species) and Acanthocephala (1espécie). This study contributed to the increase in registration for new hosts parasite species, 22 new records, and were also reported three new species of helminths in the state of Mato Grosso do Sul